Cases In Marketing Management - Bernhardt, Kenneth L., author 303796; Kinnear, Thomas C., 1943-, author 400778 (Chicago, Ill.: Irwin, 1997)
Focusing on marketing management, this text begins by orienting the student to the methods and benefits of case oriented education. It includes chapters on orientation, analyzing cases and a full case example complete with a sample student analysis of that case.